2014
DOI: 10.1007/s12663-014-0670-4
|View full text |Cite
|
Sign up to set email alerts
|

Cranioplasty Using Presurgically Fabricated Presterilised Polymethyl Methacrylate Plate by a Simple, Cost-Effective Technique on Patients With and Without Original Bone Flap: Study on 29 Patients

Abstract: Objectives The purpose of the study was to assess the clinical effectiveness of presurgically fabricated pre-sterilized polymethyl methacrylate (PMMA) plate as a cranioplasty material. Materials and MethodsThe study group consisted of 29 patients with skull defect following decompressive craniectomy. Some patients had their original bone flap preserved and some were without it. In either group presterilized prefabricated PMMA plate was used. On each visit, patients were clinically assessed; CT scans were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…18 Advantages of computer-designed, prefabricated implants have been demonstrated and include improved cosmetic outcome as well as minimization of the procedure time needed for implant insertion. 16 However, in most series, expensive commercial and industrial 3D printers (approximately US$37,000-US$310,000) or expensive com-mercial implants (approximately US$10,000) 3,5,8,13,18,21,22,26,[30][31][32] were used, which are prohibitive for use in low-and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Advantages of computer-designed, prefabricated implants have been demonstrated and include improved cosmetic outcome as well as minimization of the procedure time needed for implant insertion. 16 However, in most series, expensive commercial and industrial 3D printers (approximately US$37,000-US$310,000) or expensive com-mercial implants (approximately US$10,000) 3,5,8,13,18,21,22,26,[30][31][32] were used, which are prohibitive for use in low-and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques have been reported for customizing a cost-effective implant, with most using the head of the patient prior to or during the surgery and casting. 2,5,7,9,19,20,30,31,33 However, despite their low associated cost, these techniques are not precise or reliable, the original bone flap is needed, and the procedure involves many time-consuming steps. Recently, Abdel Hay et al published 2 cases in which a template of the external surface was used to mold the implant by hand.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is the potential for several complications, including hardware malfunction, infection, migration, and protrusion 36 . Migration and protrusion have been particularly implicated in PCH because of local inflammation, soft tissue erosion, and irritation of nociceptors 20,21,37,38 . Patients often experience pain exacerbated by palpation directly above the hardware with possible visible thinning and atrophy of their overlying scalp tissue 21 .…”
Section: Discussionmentioning
confidence: 99%
“…36 Migration and protrusion have been particularly implicated in PCH because of local inflammation, soft tissue erosion, and irritation of nociceptors. 20,21,37,38 Patients often experience pain exacerbated by palpation directly above the hardware with possible visible thinning and atrophy of their overlying scalp tissue. 21 A recent study reported an incidence of hardware removal secondary to pain and protrusion as low as 1.6%.…”
Section: Hardwarementioning
confidence: 99%
“…PEEK or titanium 3D printers can cost from US$37,000 to US$310,000, and prefabricated implants can cost up to US$10,000. [ 3 , 5 , 6 , 9 , 11 , 15 , 16 , 18 , 20 - 22 ] Price is perhaps the most important consideration in an LMIC setting such as ours, where median monthly income is approximately US$500. PMMA is an attractive option given the minimum price.…”
Section: Discussionmentioning
confidence: 99%